2013
DOI: 10.1111/hepr.12050
|View full text |Cite
|
Sign up to set email alerts
|

Warming effect on miriplatin–lipiodol suspension for potential use as a chemotherapeutic agent for transarterial chemoembolization of hepatocellular carcinoma: In vitro study

Abstract: The viscosity and injection pressure through microcatheters of MPT/LPD was confirmed to reduce significantly as the temperature is elevated. MPT/LPD warmed to 40°C has half viscosity as that at room temperature and is considered suitable for clinical use. Warming MPT/LPD may have potential to facilitate the procedure of TACE for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…[20][21][22][23][24][25] The reasons for failure include insufficient lipiodol suspension reaching the tumor due to viscosity and limited release due to insufficient embolization. New procedures for injecting miriplatin include warming to decrease viscosity, [26][27][28] which does not require replacement of the catheter.…”
Section: Any Patients With Hcc Have Hepatic Cirrhosismentioning
confidence: 99%
“…[20][21][22][23][24][25] The reasons for failure include insufficient lipiodol suspension reaching the tumor due to viscosity and limited release due to insufficient embolization. New procedures for injecting miriplatin include warming to decrease viscosity, [26][27][28] which does not require replacement of the catheter.…”
Section: Any Patients With Hcc Have Hepatic Cirrhosismentioning
confidence: 99%
“…Kora et al18 and Seko et al19 independently demonstrated that warming the MPT-Lipiodol suspension up to 40°C increased the therapeutic efficacy of TACE by reducing the viscosity of this chemotherapeutic agent. Indeed, experimental studies confirmed that the viscosity of the MPT suspension decreased as the temperature was elevated, thereby reducing injection pressure through a microcatheter 20,21. According to these studies, a lower viscosity of the MPT-Lipiodol suspension can enhance its distal delivery, thereby achieving sufficient initial accumulation of the agent in the target tumor.…”
Section: Discussionmentioning
confidence: 85%
“…[1315] One solution to this problem is to use warmed miriplatin because the viscosity of miriplatin decreases on warming. [16] It has been demonstrated in some clinical studies that miriplatin shows a higher efficacy and improves tumor control better when it is warmed; however, local tumor control rate remains unsatisfactorily low (objective response rate: 40–46.7 %). [17,18] Moreover, the temperature of administered miriplatin suspension decreases along the way to the tumor, which attenuates the warming effect.…”
Section: Discussionmentioning
confidence: 99%